Fluidez territorial e logística: o PAC no Rio Grande do Norte - Macedo, Maxsuel de Moura (2014)
The state is responsible for creating regulatory and infrastructural conditions in a determined territory. These actions generate macrodynamics, however, in some cases they show selective and restricted, as in the case concerning the transportation sector. The actions of the Brazilian government aimed at territorial fluidity nowadays are evidenced especially by the Growth Acceleration Program (PAC). The PAC in the axes allocated to the transport sector, called logistics, which in turn appears as a pressing necessity and as an ideology of the current period. Therefore, within this context of territorial transformations resulting from this program we situate our work that aims to understand how the actions of the State implemented and planned under the PAC are configuring or can configure the brazilian territorial logistics, particularly in the state of Rio Grande do Norte